Comparative analysis of selected attributes of four brands of Kalamansi (Citrus microcarpa, Bunge) concentrates - Siy, Faye Janice; Quintos, Sarah V. (1999.)
Four different brands of kalamansi concentrates were obtained. The samples were subjected to microbiological examination, physico-chemical tests and sensory evaluation. Results of the microbiological examination showed that all brands of kalamansi concentrated contain relatively low number of microorganisms, the counts ranging less than 10 - 555 cfu per gram sample. The results of the physico-chemical tests indicated that all of the samples had consistent readings for pH and soluble solids. The samples have varying ascorbic acid content, the values ranging 5.95-14.63 mg ascorbic acid per ml sample. Brand DGP had consistent readings for % titratable acidity, color, ascorbic acid content. It had, however, inconsistent readings for viscosity. The values obtained for % titrable acidity and color of brand RYM was found to be consistent. The ascorbic acid content and viscosity of the product, however, deviated from one batch to another. For brand KNT, different values were obtained for % titrable acidity, viscosity, color, and ascorbic acid content of the two batches. The difference between the ascorbic acid content of the two batches, however, was not significant. Samples of brand XWL had consistent values for color. Differences were observed in the results of % titrable acidity, viscosity and ascorbic acid content of the samples. From the results of the sensory evaluation test, brand DGP was found to be the most acceptable product. The sample was ranked between the range of like slightly and like moderately for both the concentrate and the juice. Brand KNT, on the other hand, was the least acceptable product. The panelists rated the concentrate juice with the range of dislike slightly to neither like nor dislike.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Citrus juices